An observational laboratory study to evaluate an anesthetic gas adsorber without anesthetic gas scavenging system - Katja Nickel; Christian Thoben; Christiane E. Beck; Jan Karsten; Terence Krauß; Alexander Nitschke; Moritz Hitzemann; Stefan Zimmermann; Sebastian Heiderich (BMC Anesthesiology)
Abstract Background Volatile anesthetics are known to be potent greenhouse gases and a significant source of per-and polyfluoroalkyl substances (PFAS) “forever chemical” pollution. The latter is arguably an additional strong reason to stop the emission of anesthetic exhaust gases into the atmosphere on its own. In clinical practice large proportions of used volatile anesthetics are released into the environment via anesthetic gas scavenging systems. Anesthetic gas adsorbers have been developed to bind volatile anesthetics for later extraction and reusage. They may have the potential to replace anesthetic gas scavenging systems which would have a beneficial effect on the energy consumption of hospitals. However, studies are needed to ensure effective elimination of volatile anesthetics via anesthetic gas adsorbers without gas scavenging systems. Objective To evaluate an anesthetic gas adsorber during simulated ventilation. Design A bench study. Setting An anesthesia machine was connected to an anesthetic gas adsorber (CONTRAfluran™ system, Zeosys Medical, Luckenwalde, Germany) without the use of an anesthetic gas scavenging system. A test lung was ventilated with sevoflurane and oxygen. Sevoflurane concentrations in parts per million (ppm) were detected directly from the anesthetic gas adsorber exhaust outlet using ion mobility spectrometry with gas chromatographic preseparation. A total of 6 experiments were conducted with alternating fresh gas flows, sevoflurane concentrations, humidified air and CO2 insufflation. Main outcome measures Absolute sevoflurane concentration. Results Sevoflurane concentration remained < 1 ppm as long as the canisters were not saturated. At higher fresh gas flow, the breakthrough time of the anesthetic gas adsorber decreased proportionately. Humidified air and CO2 insufflation had only a minor influence on the breakthrough time. Conclusion The anesthetic gas adsorber did not leak relevant sevoflurane concentrations through the exhaust outlet when used without an anesthetic gas scavenging system. When the canister came close to saturation, the post adsorber exhaust sevoflurane concentration progressively increased–indicated by first the yellow-light and subsequently the red-light warning of the anesthetic gas adsorber system. Continuation of the ventilation with a fully saturated canister resulted in ambient room contamination of up to 12.4 ppm sevoflurane, which though undesirable is still low when compared to mask induction.